Сложные предложения с придаточными определительными в Псковской судной грамоте - Собинникова, В.И. (Kalbotyra, 1985)
The aim of the article is to-show the heterogeneity of the language of Pskov’s Sudnaya Gramota which is also reflected in syntax, i. e. alongside with complex constructions it is abundant in colloquial phrases.